In-situ synthesis of stable ZnO-coated CsPbBr3 nanocrystals for room-temperature heptanal sensors. (December 2022) - Xuan, W.; Shan, H.; Hu, D.; Zhu, L.; Guan, T.; Zhao, Y.; Qiang, Y.; Song, J.; Zhang, J.; Sui, M.; Gu, X.; Huang, S.
Abstract: In this work, we coated perovskite quantum dots (CsPbBr3 ) with metal oxide (ZnO) by an in-situ oxidation strategy to obtain CsPbBr3 @ZnO nanocrystals, which effectively improved the moisture stability of the perovskite material. In addition, the ZnO layer can also transfer the interaction with gas molecules to the inner CsPbBr3, giving the CsPbBr3 @ZnO nanocrystals good gas-sensing properties at room temperature. This study considered CsPbBr3 @ZnO films' structural, morphological, and gas sensing properties; and simulated breath monitoring tests. Later a sensor based on CsPbBr3 @ZnO nanocrystals was prepared and used to detect the presence of heptanal (a breath biomarker for lung cancer and COVID-19) in different gases, including air, artificial breath, and real breath. The sensor displayed a fairish sensitivity ( S  = 0.36) alongside a brief response/recovery time (36.5 s/5.3 s) towards 200 ppm heptanal prepared with air, and the limit of detection could reach up to 2 ppm in the air and 3 ppm in artificial breath (made up of air, ethanol, isopropanol, 7-tridecanone, and n-tetradecane). Furthermore, the intelligent classification algorithms were used to identified the real breath samples containing heptanal (1–5 ppm) with an 82.5% accuracy rate in simulated breath monitoring tests. Theory calculation results showed that the good response to heptanal was attributed to both the positive adsorption energy (+3 eV) and the increased lattice distortion induced by heptanal. These sensors show great potential to be an effective method for early detection and treatment of lung cancer and COVID-19 for a healthy and prolonged life. We believe that this research will open the door toward more stable and practical perovskite-based sensors. Graphical abstract: Image 1 Highlights: CsPbBr3 @ZnO nanocrystals were synthesized by an in-situ method at room temperature. The sensor can detect low concentrations (few ppm) of heptanal at room temperature. The sensor showed fast response/recovery, good selectivity, and water stability. Breath with heptanal was identified in simulated breath monitoring by machine learning.